(untitled) (ALUSTATH JOURNAL FOR HUMAN AND SOCIAL SCIENCES, 2025)
Joan London (born in 1948) is an Australian author of novels, plays and short stories. She is the author of two collections of stories, Sister A-Ships (1986) and Letter to Constantine (1994). In 2001, she published her novel which is inspired by the Sumerian Epic of Gilgamesh which is a saga novel covering three generations of a family. Mrs. London, however, does not hold her to that epic, she offers it a new reading, she pours a new wine in an old bottle. The backbone in Mrs. London’s novel is the journey that Edith, the heroine takes in search for Aram, her illegitimate child’s father. Inspired by the journey of Gilgamesh, her journey is mainly allegorical. It is a journey that leads to maturity and wisdom. The novel is interesting from a semiological point of view because of the role the signs and symbols in conveying the themes of the novel, the plot and the characters